Single-cell transcriptomics reveals immune infiltrate in sepsis - Tu, Xusheng; Huang, He; Xu, Shilei; Li, Caifei; Luo, Shaoning (Frontiers in Pharmacology, 2023)
Immune cells and immune microenvironment play important in the evolution of sepsis. This study aimed to explore hub genes related to the abundance of immune cell infiltration in sepsis. After data download and data preprocessing using GEOquery package, a total of 61 differentially expressed genes between sepsis samples and normal samples were obtained through the limma package. T cells, NK cells, Mono cells, Megakaryocyte cells, DC cells, and B formed six separate clusters on the tSNE diagram using Seurat R package. GSEA enrichment analysis showed that sepsis samples and normal samples were related to Neutrophil Degranulation, Modulators of Tcr Signaling and T Cell Activation, IL 17 Pathway, T Cell Receptor Signaling Pathway, Ctl Pathway, Immunoregulatory Interactions Between A Lymphoid and A Non Lymphoid Cell. GO analysis and KEGG analysis of immune-related genes showed that the intersection genes were mainly associated with Immune-related signaling pathways. Seven hub genes (CD28, CD3D, CD2, CD4, IL7R, LCK and CD3E) were screened using Maximal Clique Centrality, Maximum neighborhood component, and Density of Maximum Neighborhood Component algorithms. The lower expression of the six hub genes (CD28, CD3D, CD4, IL7R, LCK and CD3E) was observed in sepsis samples. We observed the significant difference of several immune cell between sepsis samples and control samples. Finally, we carried out in vivo animal experiments, including Western Blotting, flow cytometry, Elisa and qPCR assays to detect the concentration and the expression of several immune factors.